Clinical courses and outcomes of COVID-19 associated pulmonary aspergillosis in 168 patients with the SARS-CoV-2 omicron variant - Yixuan Wang; Yan Yao; Qingfeng Zhang; Hao Chen; Yang He; Ke Hu (BMC Infectious Diseases, 2024)
Abstract Purpose We aimed to analyze the clinical features of COVID-19-associated pulmonary aspergillosis (CAPA) during the SARS-CoV-2 Omicron variant pandemic and to reveal the risk factors for CAPA and death. Methods A retrospective cohort study was conducted on 168 CAPA patients from December 8, 2022 to January 31, 2023. 168 COVID-19 patients without secondary fungal infection during this period were matched 1:1 using propensity score matching as controls. Results The incidence of CAPA was 3.8% (168/4421). Compared with patients without fungal infection, CAPA patients had a higher mortality (43.5% vs. 10.1%, P < 0.001). Patients in the death group (n = 73) were more likely to be admitted to ICU (91.8% vs. 26.3%, p < 0.001), had a shorter ICU length of hospitalization (10 (IQR, 6 ~ 16.5) days vs. 14 (IQR, 8 ~ 37) days, p = 0.012). Immunocompromised status (p = 0.023), NLR ≥ 5.7 (p = 0.004), CRP ≥ 50 mg/L (p = 0.043), and the number of antibiotics ≥ 3 (p < 0.001) were all risk factors for CAPA; NLR ≥ 5.7 (p = 0.009) and the number of antibiotics ≥ 3 (p = 0.018) were all independent risk factors for death. Conclusions During the Omicron variant pandemic, CAPA increased death and ICU length of hospitalization. The risk factors of CAPA and death obtained from the study can help us further understand the disease characteristics of CAPA and better guide our clinical decision-making.